2022
DOI: 10.1002/acr2.11428
|View full text |Cite
|
Sign up to set email alerts
|

Does Gender Impact a Diagnosis of Ankylosing Spondylitis?

Abstract: Objective The study objective was to explore differences in ankylosing spondylitis (AS) diagnosis experiences between men and women by examining the coding of health events over the 2 years preceding AS diagnosis. Methods Claims data (January 2006–April 2019) from the MarketScan databases were examined. Patients who had received two or more AS diagnoses at least 30 days apart and had at least 2 years of insurance enrollment before their first AS diagnosis were analyzed. Men were matched 1:1 to women by age, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Men and women also experienced differences in the diagnostic journey and management of disease, including differences in health care–seeking behavior, diagnostic coding, and treatment patterns, that may favor earlier detection of IBP and diagnosis of axSpA in men versus women ( 26 , 27 , 28 ). Along their journey to diagnosis, more than one half of patients in this US cohort (64.5%) received a misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Men and women also experienced differences in the diagnostic journey and management of disease, including differences in health care–seeking behavior, diagnostic coding, and treatment patterns, that may favor earlier detection of IBP and diagnosis of axSpA in men versus women ( 26 , 27 , 28 ). Along their journey to diagnosis, more than one half of patients in this US cohort (64.5%) received a misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, multivariate regression analysis revealed that fatigue occurred with greater severity and frequency in female patients (38). Indeed, gender differences exist with regard to the diagnostic journey and management of disease, including variations in healthcare that may favor the earlier detection and diagnosis of axSpA in men (51)(52)(53)(54)(55). While men with axSpA have a worse radiologic prognosis, women have a higher burden of disease and report higher levels of pain, especially in longer existing axSpA and neuropathic and widespread pain (56) that is associated with diagnostic delay and less responsiveness to TNF inhibitor (TNFi) treatment (54,55,57).…”
Section: Burden Of Disease and Residual Disease In Axspamentioning
confidence: 99%
“…46 A 5-year prospective study reported differential effects of risk factors on disease progression in both the sexeswith smoking being an important predictor in men and bisphosphonate therapy being more important in women. 47 Enthesitis and dactylitis are more common and severe in female patients, and studies report that males have acute anterior uveitis more frequently. 48 There have also been investigations reporting a lower response rate to TNFi therapy in women compared with men.…”
Section: Gender Differences and The Heterogeneity Of Diseasementioning
confidence: 99%
“…A recent study examining differences in early diagnostic coding and specialty doctor visits between men and women on their journey to a final diagnosis of AS in a commercial research database revealed marked divergences. 47 An alternate explanation for not only these recent findings, but potentially for many of the prior studies that allegedly demonstrated dissimilarities in disease phenotypes between men and women, can be explained by a cognitive bias whereby healthcare practitioners use different tools and testing mechanisms when approaching the diagnosis of AS in women versus men. We postulate that differences between the genders in SpA disease severity may be only partially linked to differences in anatomy between the two genders; however, the literature focusing on this area needs greater exploration.…”
Section: Gender Differences and The Heterogeneity Of Diseasementioning
confidence: 99%